Degree of hydrolization of gallotannins from Sumac (Rhus coriaria) on their anti-inflammatory potency in vitro - Rivas M., Alessandra (Zamorano: Escuela Agrícola Panamericana, 2019., 2019)
The sumac is a Middle Eastern flavoring spice rich in polyphenols. Polyphenols are compounds present in plants, which according to many investigations have a positive effect on chronic diseases such as cancer. The objective of this study was to hydrolyze a sumac extract in three different levels and evaluate its anti-inflammatory effect in colon cancer cells (HT-29). Completely randomized designs were used for the rhodanine assay for four hours (0-240 min); the proliferation of HT-29 cells with three concentrations of sumac extract (1, 5 and 25 mg / L) and three levels of enzymatic hydrolysis (non-hydrolyzed, partially hydrolyzed and hydrolyzed), and reverse transcriptase polymerase chain reaction using the three levels of hydrolysis with one concentration of sumac extract (5 mg / L). The enzymatic hydrolysis carried out by tannase lasted between 90 and 120 minutes. It degraded the high molecular weight tannins and converted them to gallic acid, from which 34 g/L were obtained along with smaller gallotannins. In the evaluation of cell proliferation, the positive effects of the degree of hydrolysis and the different concentrations used were observed. There was no decrease in the expression of some inflammation markers (NF-ĸB, TNF-α and IL-1β), while better results were observed with the sample of hydrolyzed particles with the rest of molecular markers (VCAM-1, TRL4, IL -8 and COX-2). It is recommended to continue this study in vivo and with other cell lines.